Ethnomedicinal Uses of Plants in Urak Town of Northern Balochistan, Pakistan - Tahira Bibi; Farah Naz Channa; Nazima Yousaf Khan; Samina Mengal; Niaz Muhammad Tareen (Indus Journal of Social Sciences, 2025)
This first report survey was commenced with an aim to document the use of medicinal plants by the local people in Urak town of Balochistan, Pakistan and its surrounding villages. A survey was performed using face to face conversations with structured open ended and close ended questionnaire and personal observations with 139 informants. The data obtained were quantitatively analyzed using the informant consensus factor (FIC), Family importance value index (FIV), Use report (UR) and use values (UVis). In total of 103 species belonging to 49 families and 100 genera were used by the local inhabitants to treat12 categories of various diseases. The most common plant families as depicted by its number of species (14 species and FIV 49%) was Lamiaceae as the dominant family. The species with greater use values were Eleagnus angustifolia (UVis 0.42), Caralluma tuberculata and Papaver somniferum (UVis 0.24 each). The highest FIC was calculated for antidote category (0.67), while the maximum number of species used to cure gastrointestinal disorders (53 species). The highest prevailing life form was herb (62%), and most remedies were prepared in the form of decoction (40%). The plant parts used commonly were leaves (31%). The medicinal plants with highest use values in the current study thus needs future phytochemical and pharmacological studies to confirm the efficacy and safety aspects of the identified plants. The present study in this region may also supplement the socio economic conditions of the people while taking into account the conservation status of this valuable natural resource.